The making of competitive bureaucracy: a case of bureaucratic reform in West Java province - Paskarina, Caroline (Cogent social sciences, 2017)
In this study, bureaucratic reform is understood as the practice of power operating through discursive process, that is, through the creation of a claim of truth on certain reform model, which subsequently is followed by disciplining practice to transform bureaucrat’s behavior. To analyze it, this study uses a case study of the implementation of Competition Funding Program to accelerate the achievement of Human Development Index in West Java Indonesia during the period of 2005-2010. The result shows how normalization and performativity is operated as technologies of power to construct an identity of innovative bureaucracy. This construction is justified by the idea of competition as a system of knowledge to produce regime of truth of competitive bureaucracy as a counter identity for conventional bureaucracy. Through normalization, bureaucracy is categorized into innovative bureaucracy (an expertise-based identity) and conventional bureaucracy (an clerical-based identity). Performativity is embodied through standardization of new procedures of work based on knowledge management to enhance expertise. The result suggests that bureaucratic reform has become the practice of power that operates on minds (through the creation of a system of knowledge) and bodies (by disciplining), which occurs simultaneously.